P238 A randomised, double-blind (sponsor-unblind), placebo controlled, cross-over study to investigate the efficacy, effect on cough reflex sensitivity, safety, tolerability and pharmacokinetics of inhaled GSK2339345 in patients with chronic idiopathic cough using an aqueous droplet inhaler. (12th November 2015) - Badri, H; Satia, I; Dockry, R; McGarvey, L; Marks-Konczalik, J; Murdoch, RD; Cheesbrough, A; Warren, F; Siederer, S; Smith, JA
Abstract : Introduction and objectives: Voltage gated sodium channels (VGSC) are important in the initiation and propagation of action potentials in the afferent sensory nerve fibres innervating the airways responsible for evoking cough. Therefore a VGSC inhibitor may be an effective anti-tussive agent, inhibiting cough irrespective of the type of stimuli. We aimed to investigate the efficacy of a novel use-and frequency-dependent VGSC inhibitor (GSK2339345) in patients with chronic idiopathic cough. Methods: We performed a two-part randomised, double-blind, placebo-controlled, cross-over study recruiting patients with chronic idiopathic cough from two specialist clinics. In the first part of the study, patients were randomly assigned to receive two inhaled doses of either GSK2339345 or placebo, 4 h apart during three study periods. The primary endpoint was the objective cough frequency (VitaloJAK, Vitalograph Ltd) during the 8 h post-treatment (4 hrs following each dose). The difference between GSK2339345 and placebo in log-transformed cough counts was investigated using a mixed effects model with fixed effects terms for treatment and period, and subject fitted as a random effect. In the second part, subjects attended on four study days, and underwent full dose-response cough challenges with capsaicin and citric acid following single doses of GSK2339345 or placebo. This was analysed using dose response modelling. Results: Of 16 patients enrolled (56.7 ± 9.6 yrs; 13 female), 11 completed the study. Eight hour cough counts showed a 26% increase in cough counts with GSK2339345 vs placebo. However, on exclusion of the coughs occurring within 2 min of inhalation of the study drug, there was only a 1.6% increase in coughs; see Table 1 for ratio of adjusted geometric means. There appeared to be no impact of GSK2339345 on either of the cough challenges however, the dataset was too small to draw definitive conclusions. Conclusion: There was no evidence of an anti-tussive effect of GSK2339345 over the 8 h analysis for any subject, despite cough frequency being highly reproducible within patients. Inhalation of GSK2339345 had a pro-tussive effect in all subjects following actuation of the device, not seen with placebo. The novel cough challenge methodology warrants further investigation as a development tool.